Acute Leukemia in Children - K.V. Vilchevska; S.A. Kolomenska; K.M. Marchenko (Zaslavsky O.Yu., 2014)
The lecture presents current data on the etiology, pathogenesis, clinical manifestations, observation methods and principles of treatment of children with acute lymphoblastic leukemia. own clinical observation of development of the acute lymphoblastic leukemia clinical picture in a child aged 4 years old has been described. This case is characterized by late diagnosis and inappropriate prescription of steroids in combination with antipyretic agents that led to tumor resistance to the treatment.